Biosynthesis of selenium nanoparticles by Azoarcus sp. CIB. Issue 1 (December 2016) - Fernández-Llamosas, Helga; Castro, Laura; Blázquez, María; Díaz, Eduardo; Carmona, Manuel
Abstract Background Different bacteria have been reported so far that link selenite resistance to the production of metallic selenium nanoparticles (SeNPs). Although SeNPs have many biotechnological applications in diverse areas, the molecular mechanisms involved in their microbial genesis are not fully understood. TheAzoarcus genus is a physiologically versatile group of beta-proteobacteria of great environmental relevance.Azoarcus sp. CIB is a facultative anaerobe that combines the ability to degrade under aerobic and/or anaerobic conditions a wide range of aromatic compounds, including some toxic hydrocarbons such as toluene andm -xylene, with an endophytic life style in the root of rice. We unravel here an additional physiological feature of the strain CIB that is related to its resistance to selenium oxyanions and the formation of SeNPs. Results This work is the first report of a member of theAzoarcus genus that is able to anaerobically grow in the presence of selenite. Electron microscopy preparations and X-ray spectroscopy analyses demonstrate the reduction of selenite to spherical electron-dense SeNPs whose average size was 123 ± 35 nm of diameter. Our data suggest that the main molecular mechanism of selenite resistance resides on an energy-dependent selenite exporter.Azoarcus cells trigger the synthesis of SeNPs when they reach the stationary-phase of growth, and either the exhaustion of electron donor or acceptor, both of which lead to starvation conditions, produce the reduction of selenite to red elemental selenium.Azoarcus becomes a promising biocatalyst, either as whole cells or cellular extracts, for the anaerobic and/or aerobic green synthesis of SeNPs. Conclusions Azoarcus turns out to be a new eco-friendly system to reduce selenite and produce spherical SeNPs. Moreover, this is the first report of a rice endophyte able to produce SeNPs. SinceAzoarcus is also able to degrade both aerobically and anaerobically toxic aromatic compounds of great environmental concern, it becomes a suitable candidate for a more sustainable agricultural practice and for bioremediation strategies.